A new strategy to improve the creep strength of a novel G115 steel by accelerating the precipitation of nano-sized MX and Cu-rich particles. (November 2022) - Zhang, Jingwen; Yu, Liming; Gao, Qiuzhi; Liu, Chenxi; Ma, Zongqing; Li, Huijun; Liu, Yongchang; Wang, Hui
Abstract: A new thermo-mechanical treatment strategy is proposed to improve the creep resistance of a recently developed G115 steel. The goal of this strategy is to construct a favourable microstructure with superior thermal stability at high temperatures up to 650 °C. The improved creep strength can be ascribed to the reinforced interactions between dislocations and nano-sized MX and Cu-rich precipitates. Creep analysis suggests that these MX and Cu-rich particles exhibit more important contribution to the creep resistance than the M23 C6 carbides. Following this strategy, the creep rupture life of the G115 steel can be significantly prolonged by more than two times. Graphical abstract: Image, graphical abstract